EKSPLORASI GAMELAN GENDER JAWA PADA PEMBELAJARAN MATEMATIKA - Maheswari, Sasikirana Zahra; Azka, Raekha (Jurnal Lingkar Mutu Pendidikan, 2024)
Gender is one of the gamelan instruments originating from Java. This musical instrument is one of the local cultures. From this culture there are forms, buildings, carvings, and jewelry that can be associated with mathematics. Therefore, the purpose of this study is to describe the results of the exploration of gamelan gender in mathematics learning. The method used is descriptive qualitative research method with ethnographic approach. The data collection technique comes from literature study. From gender musical instruments, it can be seen that there are mathematical concepts in the fields of geometry and geometric transformation. The results of the geometry field are in the material of rectangular flat shapes, trapezoids, circles and block and tube spaces. Then in geometry transformation is the concept of reflection and translation. So that gender musical instruments are not only used in gamelan ensembles, but can also be a means to learn mathematical concepts